THE INTERFERENCE OF SOME ENGLISH WORDS TO INDONESIAN USER - Fachri Yunanda (English Language Teaching Prima Journal (ELT), 2019)
Abstract This study focuses on the interference of some English words to Indonesian user i.e the inclusion of English words in Hilman’s Dancing on the Valentine - one of the famous teenager novel. The inclusion of English words in the novel can be caused by the educational background, bilingualism, prestige, euphemism, and belief of the author. All of the factors can make the readers especially teenagers feel relax as they can make their taste. Keywords: interference, English words